The Readiness of Special Education Teachers in Teaching Basic Vocational Skills for Agriculture - Mohamed, Suziyani; Derapa, Nurul Farahah; Satari, Nor Atiqah (Journal of Technical Education and Training, 2020)
Basic Vocational Skills is a new component introduced in Secondary School Standard-Based Curriculum for Special Education since 2017. Seven basic vocational skills have been introduced in this course, and one of it is Basic Vocational Skills for Agriculture. Therefore, this study investigated special education teachers’ readiness in teaching Basic Vocational Skills for Agriculture. Does teachers’ readiness influence by their experience in teaching Agricultural Integrated Living Skills and attendance in-service agriculture training or not. This research also examined the relationship between teachers’ readiness with the constraint faced by them in teaching Agriculture. A total of 60 special education teachers from Special Education Integrated Program were involved in this study. The purposive sampling technique was used in sample selection to make sure all the respondent had experience in teaching Basic Vocational Skill for Agriculture. A questionnaire with five points Likert scale distributed to the respondent, and they were given two weeks to complete the questionnaire. The questionnaire consists of five sections, which is, demography information, teachers’ skills, teachers’ knowledge, teachers’ attitude, and constrain faced by teachers in teaching Basic Vocational Skills for Agriculture. Respondent rated their level of agreement with various statements regarding skills, knowledge, and attitude and constrained in teaching Agricultural Integrated Living Skills. Results suggested that effective teaching process Agriculture, the teacher need knowledge, skills and attitude. It can help the student with learning disabilities to have knowledge and skills in agriculture.